2014
DOI: 10.1590/s0034-737x2014000100004
|View full text |Cite
|
Sign up to set email alerts
|

O manejo da copaíba pelas etnias Arara e Gavião na Terra Indígena Igarapé Lourdes, Rondônia, Norte do Brasil

Abstract: The production potential of oleoresin from 100 retapped and 36 first-time tapped trees of Copaifera multijuga Hayne was evaluated in the Indigenous Land Igarapé Lourdes (territory of Arara and Gavião ethnicities), Rondônia. The diameter at breast height (DBH) and the amount of oleoresin exuded was measured for each tree and the individuals were identified based on dendrological characteristics. The results indicate that relative frequency of yielding trees had similar pattern between retapped (39%) and those t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
1
4
0
2
Order By: Relevance
“…AGE AND GROWTH AFFECT OLEORESIN YIELD FROM COPAIBA TREES IN THE CERRADO-AMAZONIA ECOTONE and the average yield of copaiba oleoresin was within the range reported in this study (Alencar, 1982;Baima et al, 1999;Plowden, 2003;Oliveira et al, 2006;Rigamonte-Azevedo et al, 2006;Barbosa et al, 2009;Newton et al, 2011;Martins et al, 2013;Souza and Higuchi, 2014).…”
Section: Cernesupporting
confidence: 83%
See 2 more Smart Citations
“…AGE AND GROWTH AFFECT OLEORESIN YIELD FROM COPAIBA TREES IN THE CERRADO-AMAZONIA ECOTONE and the average yield of copaiba oleoresin was within the range reported in this study (Alencar, 1982;Baima et al, 1999;Plowden, 2003;Oliveira et al, 2006;Rigamonte-Azevedo et al, 2006;Barbosa et al, 2009;Newton et al, 2011;Martins et al, 2013;Souza and Higuchi, 2014).…”
Section: Cernesupporting
confidence: 83%
“…The distribution of productive trees with regard to DBH is similar to the results obtained in other studies, which verified that individuals with smaller diameters were less productive or completely non-productive. The intermediate classes showed higher values for oleoresin yield, whereas individuals in the higher diameter class were less productive or non-productive, as in the lower diameter class (Alencar, 1982;Plowden, 2003;Rigamonte-Azevedo et al, 2006;Barbosa et al, 2009;Souza and Higuchi, 2014).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, some studies found that Copaifera spp. trees with smaller and larger diameters tend to produce little or no oleoresin, with the intermediate diameter classes having the greatest yields (Alencar, 1982;Barbosa et al, 2009;Medeiros et al, 2018;Plowden, 2001;Rigamonte-Azevedo et al, 2006;Roquette et al, 2018;Souza & Higuchi, 2014). DBH is related to the age of trees, but in natural forests there is a greater variation in this relationship due to the complex interactions present in the ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…samples in the lowest DBH class (30 cm -42 cm) were not productive. Other studies have also pointed out that trees with DBH less than 40 cm are not productive or produce low quantity of oleoresin (Alencar, 1982;Barbosa et al, 2009;Medeiros & Vieira, 2008;Medeiros et al, 2018;Plowden, 2001;Rigamonte-Azevedo et al, 2006;Souza & Higuchi, 2014). Therefore, the data from Copaifera spp.…”
Section: Adjustment To the Equations Estimating The Oleoresin Yieldmentioning
confidence: 99%